2011
DOI: 10.1039/c1cc10620a
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol and derived solvents: new sustainable reaction media for organic synthesis

Abstract: The rapid growth of the biodiesel industry has led to a large surplus of its major byproduct, i.e. glycerol, for which new applications need to be found. Research efforts in this area have focused mainly on the development of processes for converting glycerol into value-added chemicals and its reforming for hydrogen production, but recently, in line with the increasing interest in the use of alternative greener solvents, an innovative way to revalorize glycerol and some of its derivatives has seen the light, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
111
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(119 citation statements)
references
References 127 publications
1
111
0
7
Order By: Relevance
“…Glycerol has been shown to be an interesting alternative for different organic synthesis [3,4] as for instance selective reduction of aldehydes, ketones and ␤-ketoesters with NaBH 4 [5]. Several other examples have been gathered in a review by Diaz-Alvarez et al [6]. Studies by Jérôme and Gu [7][8][9], have shown that, in some reactions, such as the Aza-Michael reaction of p-anisidine and the Michael reaction of indole, glycerol used as solvent is capable to achieve yields up to 80% under catalyst-free conditions, these yields being higher than those obtained with usual solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Glycerol has been shown to be an interesting alternative for different organic synthesis [3,4] as for instance selective reduction of aldehydes, ketones and ␤-ketoesters with NaBH 4 [5]. Several other examples have been gathered in a review by Diaz-Alvarez et al [6]. Studies by Jérôme and Gu [7][8][9], have shown that, in some reactions, such as the Aza-Michael reaction of p-anisidine and the Michael reaction of indole, glycerol used as solvent is capable to achieve yields up to 80% under catalyst-free conditions, these yields being higher than those obtained with usual solvents.…”
Section: Introductionmentioning
confidence: 99%
“…(Ahluwalia and Varma 2009). Although no perfect green solvent exists that could be applied in all situations, several alternatives have recently been developed (i.e., solvents from biomass, ionic liquids, supercritical fluids, etc.) (Diaz-Alvarez et al 2011). Solvents from biomass can be obtained by enzymatic or esterification and fermentation processes.…”
Section: Introductionmentioning
confidence: 99%
“…O glicerol possui ainda a vantagem de solubilizar facilmente compostos orgânicos, o que o torna apto para ser utilizado como meio reacional em síntese orgânica. 12 Desde os trabalhos seminais de …”
Section: Introductionunclassified